The role of service quality on customer satisfaction and customer loyalty in Philippine healthcare: Case study of De La Salle University Medical Center - Gutierrez, Roneena M. (Animo Repository, 2022)
The study investigates the relationship of service quality and customer loyalty with the mediating effect of satisfaction in the Philippine healthcare industry. Aside from evaluating the overall service quality, the five service quality dimensions were also examined separately in order to determine which of the service quality facets are of most importance when evaluating the satisfaction and loyalty of patients in the Philippine context. The research study utilized quantitative methods of data collection wherein correlational, causal or explanatory, and descriptive research designs were used in this study. Data was collected through a questionnaire with a sample size of 227 patients from De La Salle University Medical Center. Interviews were also conducted to gather supporting information from the quantitative data gathered. The hypotheses were tested using Baron and Kenny’s method for mediation and causal mediation analysis. The results of the study indicate that service quality had a significant positive effect on both customer satisfaction and customer loyalty. Furthermore, customer satisfaction partially mediates the relationship between service quality and loyalty. As for the dimensions, it was found that empathy, responsiveness, assurance, and reliability had significant positive effects on customer satisfaction. On the other hand, empathy, tangibility, responsiveness, and reliability had significant positive effects on customer loyalty.